The appearance of the body in dress culture - Devetak, Tanja (Anthropological notebooks, 2025)
This study explores the inseparable relationship between body appearance and dress culture in the contemporary Euro-American context, with particular attention to body movement, gender distinctions, phenomenological embodiment, presentation and the virtual body. Drawing on phenomenology, fashion studies, cultural sociology, and body theory, it examines how the clothed body co-constructs meaning in both individual ex- perience and collective social contexts. The research aims to analyze the phenomenolog- ical dimensions of embodiment in dress, to explore clothing as a medium for identity construction and social communication, and to develop a framework that reflects the complexity of bodily experience within fashion systems. Methodologically, the study combines theoretical analysis, cultural critique, case study research on fashion design practices and participant observation. The study’s key innovation is the original catego- rization of the body into four interrelated dimensions: as user, producer, representation and digital self. This model provides a novel analytical lens to understand how bodies operate across dressing practices, production systems, fashion media and virtual envi- ronments. The findings show that the body is not a passive recipient of clothing, but an active agent of cultural meaning shaped by aesthetic norms, sociopolitical systems and digital technologies, thus offering a new perspective on embodiment in dress culture.
Keywords: body; dress culture; fashion; identiteta; identity; kultura oblačenja; moda; telo